SSW (Surabaya Single Window): Inovasi Sistem Pelayanan Terintegrasi Berbasis Elektronik terhadap Perwujudan Akuntabilitas Publik Unit Pelayanan Terpadu Satu Atap Kota Surabaya - Indah Putri Pradhina; Teguh Yuwono (Journal of Politic and Government Studies, 2019)
Public service is an inseparable part of the state’s obligation to prosper its people and is the basic essentials for the realization of social justice. Along with the current development, public services are carried out in various forms of innovation, especially by utilizing technology. Through an electronic-based public service, effectiveness, efficiency, and transparency are expected to be realized. The city of Surabaya is one of the cities in Indonesia that has implemented e-government in carrying out its government affairs to realizeaccountable and transparent public service principles. From the various innovations that have been implemented by the Government of Surabaya City, there is an electronic-based licensing service system called Surabaya Single Window (SSW).The research method used in this research is descriptive qualitative method, with data collection techniques in the form of observation, interviews, questionnaires, and documentarystudies. The data obtained are then analyzed using triangulation methods, theories, and data sources, as well as reliability.The results obtained were SSW implementation based on 6 (six) variables that influence implementation performance according to van Meter and van Horn theory, which are policy standards and targets; resources; relationships between organizations; policy implementor characteristics; social, political, and economic conditions; and the disposition of the implementor as a whole has been declared good. Although there are still some obstacles, the Surabaya One-Stop Integrated Services Unit (UPTSA) has been able to make various efforts to overcome them. In addition, because the products produced by UPTSA are licensing servicesavailable on SSW, it can be stated that the performance of SSW implementation has an effect on the realization of UPTSA Surabaya’s public accountability. In this regard, accountability and the index of community satisfaction for each agency also stated to be good. In addition, the form of accountability carried out by UPTSA Surabaya City itself is through LAKIP/SAKIP, e-performance filling, and monthly performance presentations by each division.Keywords: Innovation, E-Government, Public Service, Policy Implementation, Accountability